Reforming the Departmental Higher Education Institutions: A Critical Analysis - V. V. Bulgakov (Высшее образование в России, 2019)
The results of the reform of Russian higher education widely discussed among the pedagogical and expert community are characterized by the ambiguity and inconsistency of assessments. Special attention should be given to the need and results of the reforming in relation to the departmental universities of the power block which ensure the implementation of the country’s security functions. The features of the organization of the educational process in the departmental higher educational institutions of the power block are presented on the example of educational organizations of the EMERCOM of Russia system, starting from the entrance examinations stage and ending with the employment of graduates. The article considers the main directions of reforming the Russian higher education institutions and presents a critical analysis of their implementation in relation to departmental educational organizations of higher education of the power bloc. The peculiarities of the activities of departmental educational organizations of the power block, the tasks to be solved and the functions performed related to the training of specialists in the field of ensuring the security of a country require a balanced approach from the government education authorities when implementing measures aimed at the maximum integration of the higher education system into the global education system.